Combining multiomics to analyze the molecular mechanism of hair follicle cycle change in cashmere goats from Inner Mongolia - Zhang, Chongyan; Qin, Qing; Liu, Zhichen; Wang, Yichuan; Lan, Mingxi; Zhao, Dan; Zhang, Jingwen; Wang, Zhixin; Li, Jinquan; Liu, Zhihong (Frontiers in Veterinary Science, 2024)
Inner Mongolia Cashmere Goat is a local excellent breed of cashmere and meat dualpurpose, which is a typical heterogeneous indumentum. The hair follicles cycle through periods of vigorous growth (anagen), a regression caused by apoptosis (catagen), and relative rest (telogen). At present, it is not clear which genes affect the cycle transformation of hair follicles and unclear how proteins impact the creation and expansion of hair follicles. In this work, we investigated the possible pathways of transformation and apoptosis in goat hair follicles using multi-omics joint analysis methodologies. The results showed that 917 , 1187 and 716 proteins were specifically expressed in anagen, catagen and telogen. The result of gene ontology (GO) annotation showed that differentially expressed proteins(DEPs) are in different growth cycle periods, and enriched GO items are mostly related to the transformation of cells and proteins. The Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment result indicated that the apoptosis process has a great impact on hair follicle's growth cycle.The results of the protein interaction network of differential proteins showed that the Ribosomal Protein family ( RPL4, RPL8, RPS16, RPS18, RPS2, RPS27A, RPS3 ) was the core protein in the network. The results of combined transcriptome and proteomics analysis showed that there were 16,34, and 26 overlapped DEGs and DEPs in the comparison of anagen VS catagen, catagen VS telogen and anagen VS telogen, of which API5 plays an important role in regulating protein and gene expression levels. We focused on API5 and Ribosomal protein and found that API5 affected the apoptosis process of hair follicles, and Ribosomal Protein was highly expressed in the resting stage of hair follicles. They are both useful as molecular marker candidate genes to study hair follicle growth and apoptosis, and they both have an essential function in the cycle transition process of hair follicles. The results of this study may provide a theoretical basis for further research on the growth and development of hair follicles in Inner Mongolian Cashmere goats.